China and Russia Security Cooperation on Arms Exports Toward the US’ Global Hegemony - Kusuma, Sigit Candra Wiranata; Ngambut, Aurelia V. T.; Christina, Novelia (WILAYAH: The International Journal of East Asian Studies, 2021)
Abstract: The purpose of this paper is to analyse China and Russia’s relationship in terms of arms exports between both countries and its implications for the United States (US) using a qualitative method and the conceptual framework of Neorealism: hegemony and security cooperation. China and Russia are two great powers that have maintained close diplomatic ties since the Cold War Era. Both China and Russia cooperate in various sectors, including security. Since the collapse of the SU (USSR), which marked the establishment of post-Cold War Russia, the country has become a major arms exporter to China. This close relationship has dynamically developed in the last few decades. China-Russia security cooperation has been assessed as a security challenge for the US. The security cooperation between China, the new rival for the US since its rising, and Russia, the US’ former superpower rival in the Cold War era, is interpreted as a threat to US domination in the Asia-Pacific. However, this paper concludes that while China and Russia have a close relationship, China can surpass Russia’s military technology. That is why, although these countries relationships are close and Russia does not see China as its primary threat, this does not mean that Russia will let its guard down in facing China’s development. There is a tri-polar power balance between these countries and with the US. The main worry is if two actors get too close, leaving the remaining state isolated. Regardless of the global power equilibrium trajectory, China and Russia will become more closed than the US.